Training loads and heart rate variability of young skiers - Anpilogov, I. E.; Pavlov, P. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to evaluation of the changes in the relationships and fluctuations between the indicators of heart rate variability in young skiers during a training session.